The role of parents in fostering an interest in television programmesand computer games in pre-school children - Potembska, Emilia (Current Problems of Psychiatry, 2011)
Contemporary children are eager to play computer games and watch TV as these eliminate the sense of boredom and fill the time when the parents are busy working. Computer games and movies available on the market are full of aggression and violence. Children who watch violent scenes may want to imitate aggressive behaviour in real life. The aim of the study was to analyze television programmes watched by pre-schoolers and computer games bought for them by their parents. An answer was given to the question of why computer games are attractive to pre-school children. Participants: The participants were 91 children (54% girls and 46 boys) aged 4-6 years old. 87% of the participants were being brought up in complete families. Results: In the study, the children’s answers to the following questions were analyzed: "do your parents play with you?", "do you use the computer?", "do you like to play computer games and why?, and "how are you punished by your parents?" About 32% of the children said that their parents did not play with them because "they worked late hours" and that "mum had no time because she was busy cooking". 90% of the surveyed pre-schoolers liked using the computer and playing computer games, and 67% reported that they received computer games from their parents because they asked for them or as a reward for good behaviour or because the parents did not want them to "get bored". The parents of 36% of the participants punished their offspring by not allowing them to use the computer or to watch TV. Conclusions: Computer games and television should not be treated by parents as ways of getting some rest, but ought to provide an opportunity to spend time together with the child, to play and learn in each other’s company. By using movies and computer games to reward their children, allowing computers to replace their children’s interactions with peers, and by failing to control the amount of the time spent by their children in front of a computer or TV screen, adults may contribute to the development of computer or Internet addiction in their children’s adult lives.